Particularities of coronary physiology in patients with atrial fibrillation: insights from combined pressure and flow indices measurements - Pintea Bentea, Georgiana; Berdaoui, Brahim; Samyn, Sophie; Morissens, Marielle; van de Borne, Philippe; Castro Rodriguez, Jose (Frontiers in Cardiovascular Medicine, 2023)
Background. Symptoms suggestive of myocardial ischemia are frequently encountered in patients with atrial fibrillation (AF) even in the absence of obstructive coronary artery disease. Nevertheless, an in-depth characterisation of coronary physiology in patients with AF is currently lacking. Objectives. We aim to provide an insight into the characteristics of coronary physiology in AF, by performing simultaneous invasive measurements of coronary flow- and pressure- indices in a real-life population of patients with AF and indication of coronary angiography. Methods. This is a prospective open label study including patients with permanent or persistent AF and indication of coronary angiography showing intermediate coronary stenosis requiring routine physiological assessment (n=18 vessels from 14 patients). We measured FFR (fractional flow reserve), and Doppler-derived coronary flow indices, including CFR (coronary flow reserve) and HMR (hyperaemic microvascular resistance). Results. From the analysed vessels, 18/18 vessels (100%) presented a pathological CFR (<2.5), indicative of coronary microvascular dysfunction (CMD), and 3/18 (17%) demonstrated obstructive epicardial coronary disease (FFR ≤ 0.8). A large proportion of vessels (15/18; 83%) showed discordant FFR/CFR with preserved FFR and low CFR. 47% of the coronary arteries in patients with AF and non-obstructive coronary epicardial disease presented structural CMD (HMR≥2.5mmHg/cm/s), and were associated with high BMR and an impaired response to adenosine. Conversely, vessels from patients with AF and non-obstructive coronary epicardial disease with functional CMD (HMR<2.5mmHg/cm/s) showed higher bAPV. The permanent AF subpopulation presented increased values of HMR and BMR compared to persistent AF, while structural CMD was more often associated with persistent symptoms at 3 months, taking into account the limited sample size of our study. Conclusion. Our findings highlight a systematically impaired CFR in patients with AF even in the absence of obstructive coronary epicardial disease, indicative of CMD. In addition, patients with AF presented more prevalent structural CMD (HMR≥2.5mmHg/cm/s), characterized by reduced hyperaemic responses to adenosine, possibly interfering with the FFR assessment.